Financial Performance Evaluation Between Traditional Bank and Digital Bank During Digital Transformation: Evidence From Indonesia - Ahmad Jihan Tamami; Tony Irawan; Dikky Indrawan (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The COVID-19 pandemic accelerated the transformation of the financial sector by significantly altering consumer behavior. This shift led to the rise of digital banks as replacements for traditional banks. However, some digital banks have underperformed compared to their initial performance or after undergoing mergers and acquisitions.Purpose: This study aims to analyze the financial performance of traditional banks before their digital transformation, providing insights to inform alternative strategies for digital banking.Design/Methodology/Approach: The research examines the financial performance of nine banks (four digital banks and five traditional banks) from 2019 to 2022. The performance metrics include liquidity ratio (Loan-to-Deposit Ratio, LDR), solvency ratio (Equity-to-Asset Ratio, EAR), profitability ratios (Net Interest Margin, NIM, and Return on Assets, ROA), and activity ratio (Total Asset Turnover, TATO). Data were collected online from the Financial Services Authority website, and the analysis was conducted using descriptive statistics, parametric tests (Paired Samples t-Test), and non-parametric tests (Mann-Whitney U Test).Findings/Results: The study finds that after transitioning to digital banks, there is a significant increase in the solvency ratio (EAR) but a notable decline in profitability (ROA) and activity (TATO). Compared to traditional banks, digital banks exhibit lower LDR and ROA but higher EAR and NIM.Conclusion: The study highlights key financial performance aspects associated with digital bank transformation. The findings suggest that enhancing financial performance requires improving liquidity, solvency, profitability, and activity ratios. Strategies include engaging with the digital ecosystem, acquiring new customers through innovation, consumer-focused financing, and strengthening core capital.Originality/Value (State of the Art): This research uniquely applies multiple financial performance parameters to compare digital banks before transformation with traditional banks in Indonesia. It identifies potential strategies to address challenges faced by digital banks, enhancing academic understanding and offering practical solutions to improve their financial performance. Keywords: digital bank, digital transformation, financial performance, traditional bank